Pengembangan Bahan Ajar Matematika Berbasis CTL Kelas IV KD 3.1 dan 3.2 Kurikulum 2013 - fauzia, indria; dalais, mursal; ahmad, syafri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this study is to develop mathematics teaching materials based on CTL class IV KD 3.1 and 3.2 Curriculum 2013 which are valid, practical and effective. This type of research is development research that refers to the model proposed by Branch with the analysis phase, design, develop, implementation and evaluation. This research was conducted in Class IVa 15 Ulu Gadut elementary school with a total of 25 students. The results of the validation of teaching materials by the three validators reached a very valid category. The average practicality test of the teacher's response questionnaire is 96.4% with a very practical category. The average practicality test of the response questionnaire of students is 96% with a very practical category. The results of the average effectiveness test seen from the increase in completeness of students reached 84%. This indicates that teaching materials developed are effective because ≥75% of students experience an increase in their learning outcomes. It can be concluded that mathematics teaching materials based on CTL class IV KD 3.1 and 3.2 2013 curriculum are valid, practical and effective